HIV/AIDS Knowledge Among Adult Male Migrant Factory Workers of An Industrial City in North India - SA Rizwan; Sanjay Rai; Kiran Goswami; Puneet Misra; Shashi Kant (Medsci Publications, 2015)
Backgraound: Male migrant workers are considered an important risk group for propagation of HIV/AIDS in concentrate epidemic situation like that seen in India. Aim of the study was to describe the socio-demographic profile and  HIV/AIDS  knowledge  of adult male migrant workers in an industrial city in north India. Method: It was a cross sectional survey conducted in 2011. Male migrant workers aged ≥18 years, who were born outside Harya- na, who had moved to current location after 15 years of age, who had worked in current factory for at least one year were eligible for face-to-face interview using semi-structured questionnaire. Knowledge score was calculated by taking into account 22 varia- bles. Total score range was 0 to 22 and was classified into three categories as ≥80% (comprehensive), 50% to 79% (moderate) and ≤49% (poor). Results: A total of 755 completed the interview. About 50% of the men had migrated before 21 years of age and their mean (SD) du- ration of migration was 9.5 (6.7) years. Several misconceptions such as transmission through mosquito bite, kissing on cheeks and hugging, and prevention by not sharing utensils were preva- lent. Mean (SD) knowledge score was 14.7 (6.6). Almost 60% of participants did not have comprehensive HIV/AIDS knowledge. Conclusion: This study reveals that there is an urgent need to fill knowledge gaps among migrant workers that may prove vital to prevent further spread of HIV/AIDS in concentrated epidemics.